Public Expenditure And Property Cycle: The Case In Shanghai - Yat , Hung Chiang; Lennon , H. T. Choy; Li, Jing (Penerbit Universiti Sains Malaysia, 2012)

(untitled)
China's economic growth heavily relies on fixed asset investment. Previous studies have demonstrated that GDP growth plays a key role in assessing Chinese local officials' performance and enhancing their chances of political promotion. Thus, local officials have a strong motivation to boost the economy, which also impacts the property market. Based on this notion, the empirical results of this study indicate that public expenditure fluctuations and residential property price movements in Shanghai were positively co-integrated from 1992 to 2009, suggesting that increased public expenditure has reshaped Shanghai's property cycle to have longer booms and shorter busts. The findings also shed light on the nature of property cycles in other large- and medium-sized Chinese cities and developing countries with rampant economic growth, low real interest rates and an increasing urban population.